Contributing Factors of Lumbar Puncture Refusal in Children Presented with Suspected Meningitis - Hassan Asif, Sobia Shahalam, Shazia Rizwan, Rizwan Waseem, Tayyaba Noor, Madiha Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To study frequency of contributing factors of lumbar puncture refusal in children presented with suspected meningitis. Methodology: In this descriptive cross-sectional study during 2019 to 2020 at Pediatric Department Ghurki Trust Teaching Hospital, Lahore a total of 155 cases of 2 months to 12 years of age who presented with suspected meningitis and refused the procedure were included. They were asked about various contributing factors like fear of side effects, little knowledge of the disease, unsuccessful experience and lack of medical facility. Results: In this study there were total 155 cases. Out of these 84 (54.19%) were males and 71 (45.81%) females. The mean age of the participants was 3.81±2.03 years. Among contributing factors for refusal, most common factor was fear of side effect which was observed in 39 (25.16%), followed by unsuccessful experience seen in 18 (11.61%), lack of medical facility seen in 16 (10.3%) and little knowledge of the disease in 13 (8.39%) of the cases. There was no significant association with any of the contributing factor with variable of this study. CONCLUSION: There are number of factors for refusal of LP and fear of side effect was the most common. There was near significant association of high socioeconomic class with lack of medical facility. Keywords: Lumber puncture, CSF, Medical Facility, Fear